2009
DOI: 10.1603/029.102.0509
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Irradiation Dose for Sterility Induction and Quality of <I>Bactrocera tryoni</I>

Abstract: The current study is an important step toward calibrating, validating, and improving irradiation methods used for Bactrocera tryoni (Froggatt) sterile insect technique (SIT). We used routine International Atomic Energy Agency/U.S. Department of Agriculture/Food and Agriculture Organization quality control tests assessing percentage of emergence, flight ability, sex ratio, mortality under stress, reproductive sterility, and sexual competitiveness, as well as a nonstandard test of longevity under nutritional str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

15
75
4
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(95 citation statements)
references
References 23 publications
15
75
4
1
Order By: Relevance
“…In that study, all irradiation doses achieved adequate reproductive sterility (Ͼ99.5%), with the 60 Gy treatment providing mean sterility of 99.98%. Furthermore, this study found that longevity under crowding stress (FAOÐ IAEAÐUSDA 2003) correlated negatively with irradiation dose, and that sexual competitiveness steadily decreased with increasing irradiation dose (Collins et al 2009). These results strongly suggest that reduced irradiation dose would be beneÞcial to ßy quality and would not sacriÞce adequate sterility (see also Collins and Taylor 2011).…”
mentioning
confidence: 64%
See 4 more Smart Citations
“…In that study, all irradiation doses achieved adequate reproductive sterility (Ͼ99.5%), with the 60 Gy treatment providing mean sterility of 99.98%. Furthermore, this study found that longevity under crowding stress (FAOÐ IAEAÐUSDA 2003) correlated negatively with irradiation dose, and that sexual competitiveness steadily decreased with increasing irradiation dose (Collins et al 2009). These results strongly suggest that reduced irradiation dose would be beneÞcial to ßy quality and would not sacriÞce adequate sterility (see also Collins and Taylor 2011).…”
mentioning
confidence: 64%
“…Performance of sterile ßies is dependent on a wide range of factors, including diet and production methods, irradiation dose, handling and transport stress, release methods, and Þeld conditions (Meats and Edgerton 2008, Campbell et al 2009, Collins et al 2009, Fanson et al 2009, Dominiak et al 2011a, Weldon and Taylor 2011. Consequently, SIT programs are continuously researching new methods to improve ßy quality and hence SIT success.…”
mentioning
confidence: 99%
See 3 more Smart Citations